An Examination of the Intracorrelation of Family Health Insurance - Marion Aouad (Institute of Labor Economics (IZA), 2021)
A negative shock to one household member can have consequences for other household members. This paper demonstrates the extent of job lock and health insurance plan stemming from the unanticipated health shock of a child family member. In response to the shock, I estimate a 7 – 14 percent decreased likelihood of all family members leaving the current health insurance network and health plan. This is plausibly driven by reduced rates of job switching by the plan's primary policyholder. Furthermore, switching frictions stemming from the non-portability of health insurance products may contribute to the observed job and "health plan lock."
Keywords: I10; I12; J10; J20; 330; household; health shock; health insurance; job lock